Dampak Kebijakan Penetiban Pertambangan Emas Rakyat di Kecamatan Tewah Kabupaten Gunung Mas - Saputri, Rika Jumi; Rhama, Bhayu; Suprayitno (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2022)
Tewah District is one of the areas in Gunung Mas Regency that has high gold potential, so that many people in Gunung Mas Regency, especially Tewah District, carry out gold mining as a source of income to meet the economic needs of the community. Mining activities are no longer carried out traditionally using semi-mechanical equipment with mining technology and using mercury which is harmful to the soil and damaging to the environment. People's gold mining activities in Tewah District, Gunung Mas Regency are carried out by the community on the basis of economic pressure which is increasingly difficult to fulfill, so that many people mine gold illegally without following the applicable rules. Problem formulation: 1) How is the Implementation of the Gold Mining Control Policy in Tewah District, Gunung Mas Regency? 2) What is the Impact of the Gold MiningControl Policy in Tewah District, Gunung Mas Regency? 3) What factors are the obstacles in implementing the Gold Mining Control Policy in Tewah District, Gunung Mas Regency? The research method used by the author is a qualitative research method. Qualitative research method is an on-site research to describe and analyze phenomena, events, social activities, attitudes, beliefs, receptions and thoughts of people individually or in groups. Data collection was obtained through interviews, observation and documentation. Data sources were analyzed interactively which consisted of three main things, namely: Data collection or data reduction, data presentation and conclusion drawing/verification.